A practical guide to dragons collector's set - Trumbauer, Lisa, 1963-; local; ill. Trumbauer, Lisa (Renton, WA : Mirrorstone, 2008)
Presents a two-volume boxed set about the mythical world of dragons, describing their anatomy, language, rules of combat, and life span, along with
A practical guide to dragons -- A practical guide to dragon riding.
First work originally published: Renton, WA : Wizards of the Coast, 2006. 2nd work originally published: Renton, WA : Wizards of the Coast, 2008.
"Inscribed by Sindri Suncatcher, the greatest kender wizard who ever lived."
Title from slipcase.
Issued in slipcase.
instructions on how to raise a baby dragon and how to train it for riding.
Keywords: sears; sears; sears; sears